Spore morphology of some Orthotrichaceae Arn. species (Bryophyta) from Turkey - Savaroglu, Filiz (Bangladesh Journal of Botany, 2018)
The spores of Orthotrichum lyellii Hook & Taylor, O. speciosum Nees, O. affine Schrad. ex Brid., O. rupestre Schleich. ex Schwagr., O. anomalum Hedw. and O. cupulatum Hoffm. ex Brid. showed the apertural region consists of a leptoma in their spores. Two spore types are characterized by their surface ornamentation, reflecting the species’ taxonomic relationships. The spore shape of all the species is spheroid. The spore size ranged from 7 to 23 μm in the genus Orthotrichum. While the surface ornamentation is verrucate in O. speciosum and O. affine, it is gemmate in O. lyellii, O. rupestre, O. anomalum and O. cupulatum. The spore walls of the family Orthotrichaceae include sclerine (the distinction between exine and perine might be difficult to define) and intine. The examined moss species belong to two habitat types: corticolous and saxicolous. The taxonomic and ecological implications of the genus Orthotrichum were discussed on the basis of its spore morphology.